2005
DOI: 10.1121/1.2062268
|View full text |Cite
|
Sign up to set email alerts
|

Symmetric mode resonance of bubbles attached to a rigid boundary

Abstract: Experimental results are compared with a theoretical analysis concerning wall effects on the symmetric mode resonance frequency of millimeter-sized air bubbles in water. An analytical model based on a linear coupled-oscillator approximation is used to describe the oscillations of the bubbles, while the method of images is used to model the effect of the wall. Three situations are considered: a single bubble, a group of two bubbles, and a group of three bubbles. The results show that bubbles attached to a rigid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 27 publications
(31 reference statements)
2
28
0
Order By: Relevance
“…Thus, the net effect of the mirror-image bubble ͑and hence the wall͒ was to reduce the resonance frequency of the bubble. Payne et al 20 showed that the mirror-image bubble approach can also be successfully extended to model the behavior of a group of bubbles close to a wall; predictions showed good agreement with the experimental data.…”
Section: Introductionmentioning
confidence: 80%
See 4 more Smart Citations
“…Thus, the net effect of the mirror-image bubble ͑and hence the wall͒ was to reduce the resonance frequency of the bubble. Payne et al 20 showed that the mirror-image bubble approach can also be successfully extended to model the behavior of a group of bubbles close to a wall; predictions showed good agreement with the experimental data.…”
Section: Introductionmentioning
confidence: 80%
“…As a reference, and in order to determine the frequency response of the tank itself, data from the hydrophone were initially obtained for cases when no bubbles were present in the tank. 20 Typical frequency response is shown in Fig. 6͑a͒.…”
Section: Methodsmentioning
confidence: 98%
See 3 more Smart Citations